Apoptosis repressor with caspase recruitment domain modulates second mitochondrial‐derived activator of caspases mimetic‐induced cell death through BIRC2/MAP3K14 signalling in acute myeloid leukaemia. (31st July 2014) - Mak, Po Y.; Mak, Duncan H.; Ruvolo, Vivian; Jacamo, Rodrigo; Kornblau, Steven M.; Kantarjian, Hagop; Andreeff, Michael; Carter, Bing Z.
Summary Overexpression of the apoptosis repressor with caspase recruitment domain (ARC, also termed NOL3) protein predicts adverse outcome in patients with acute myeloid leukaemia (AML) and confers drug resistance to AML cells. The second mitochondrial‐derived activator of caspases (SMAC, also termed DIABLO) mimetic, birinapant, promotes extrinsic apoptosis in AML cells. SMAC mimetics induce cleavage of cellular inhibitor of apoptosis (cIAP) proteins, leading to stabilization of the nuclear factor‐κB (NF‐κB)‐inducing kinase (MAP3K14, also termed NIK) and activation of non‐canonical NF‐κB signalling. To enhance the therapeutic potential of SMAC mimetics in AML, we investigated the regulation and role of ARC in birinapant‐induced apoptosis. We showed that birinapant increases ARC in AML and bone marrow‐derived mesenchymal stromal cells (MSCs). Downregulation of MAP3K14 by siRNA decreased ARC levels and suppressed birinapant‐induced ARC increase. Reverse‐phase protein array analysis of 511 samples from newly diagnosed AML patients showed that BIRC2 (also termed cIAP1) and ARC were inversely correlated. Knockdown of ARC sensitized, while overexpression attenuated, birinapant‐induced apoptosis. Furthermore, ARC knockdown in MSCs sensitized co‐cultured AML cells to birinapant‐induced apoptosis. Our data demonstrate that ARC is regulated via BIRC2/MAP3K14 signalling and its overexpression in AML or MSCs can function as a resistant factor to birinapant‐induced leukaemia cell death, suggesting that strategies to inhibit ARC will improve the therapeutic potential of SMAC mimetics.